Diffuse skin swelling as the initial presentation of superior vena cava syndrome caused by thoracic tumor: a case report - Shiyang LI; Xianwei CAO; Chuan WAN; Xuehua DENG; Chen YU; Hongxuan WU; Zhibin ZHANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
We present a case of superior vena cava syndrome caused by thoracic tumor with initial presentation of diffuse skin swelling. A 62-year-old female presented with facial erythema, swelling and itching for 6 months, with aggravation for 5 days. Dermatological examination showed diffuse edematous erythema on the face, with unclear boundary, fading under pressure, tight feeling of touch, nonpitting edema of the neck and upper limbs. The patient was diagnosed as allergic dermatitis in other hospital. Following the treatments with antiallergic and other symptomatic treatment, pruritus was slightly improved, but the erythema and swelling of the face were not significantly improved, and gradually aggravated. Chest multislice helieal CT showed soft tissue masses on the mediastinum and right hilum. The lesions were considered as malignant lesions involved the superior vena cava, atrium and right pleura. Formation of tumor thrombus in superior vena cava and its branches, right atrium, right superior pulmonary vein and left atrium were also seen. Diagnosis: thoracic tumors complicated with superior vena cava syndrome. Due to the concerns of medical cost and surgical risks, the patient did not receive further treatment in our hospital and was lost to follow-up.